Antimicrobials and antimicrobial resistance - Smith, Frances (2017)
Drug discovery and development is becoming increasingly harder due to scientific bottlenecks, increased regulation from approval bodies and economic circumstance. Using unusual approaches to drug discovery can fast-track the production of new antimicrobials, as is the case with drug repurposing. There is a strong need for antimicrobial agents that bacteria can’t develop resistance to and the best way to address this is by developing drugs that do not create a strong selection for resistance. Antivirulence drugs are ideal in this respect as they do not target essential biological processes. It is naïve, however, to assume that bacteria will never develop resistance to any of the antibiotics they are presented with. Careful control over the use of antibiotics should be employed to prevent the development and spread of resistance if we are to avoid the upcoming antibiotic apocalypse.